Quadrangular Fixation of Pectus Bars to Prevent Displacement in Nuss Procedure - Yoo, Gyeol; Shin, Jeonghwan; Rha, Eun Young; Jeong, Jin Yong; Lee, Jun; Noh, Giyong; Park, Soo Seog (The Thoracic and Cardiovascular Surgeon, 2020)
Background Double pectus bars are sometimes inserted to correct pectus excavatum. Method of double-bar fixation to prevent bar displacement has been rarely reported. We have used quadrangular fixation of the double pectus bars. The objective of this study was to compare results of the quadrangular fixation procedure with those of the classic separate fixation procedure.Methods From September 2011 to January 2016, 86 patients underwent Nuss procedure with double-bar insertion. In 44 patients, each bar was fixed separately (group A). In 42 patients, quadrangular fixation of the bars was performed with metal plates (group B). Patient demographics, Haller index (HI), bar displacement index (BDI), and reoperation rate were compared between the two groups.Results The mean patient age was 17.2 years (range: 3–40 years) in group A and 17.8 years (range: 4–30 years) in group B. There was no significant difference in preoperative or postoperative HIs between the two groups (all p >0.05). Early complication rates were 15.9% in group A and 9.5% in group B (p > 0.05). In group A, three patients underwent surgery to correct bar displacement (6.8% of reoperation rate), whereas there was no corrective surgery in group B. BDIs of the two groups were significantly different (p < 0.01).Conclusions When quadrangular fixation was performed with upper and lower pectus bars bilaterally fixed by connecting each bar with plates, bar displacement was prevented more effectively than separate fixation, thus minimizing reoperation.
Keywords: pectus excavatum; minimally invasive surgery; surgery; complications